Urgensi Pengelolaan Sumber Daya Manusia dalam Bisnis di Era Kontemporer - S. Suparwi (Jurnal Penelitian, 2018)
In today's globalization era companies be demanded must be able to compete with competitors who certainly not only sourced from domestic but also have to compete with competitors from abroad. The increasingly tight competition is what makes the business people must have quality human resources so that it has a good production process so that the productivity of the company can be realized. Human resources are key in every organization whether in the realm of education, politics, social, more so the business environment. although not as spaciously ancient time for its role in doing business activities but the role of human resources is quite significant and sometimes can't replaced in certain domain. Therefore, human resources as should be properly managed to function so always be productive and generate more profit for the company. Trend of human resource management in the contemporary era provides a new paradigm using information technology, so it’s very helpful in managing human resources.